An evaluation of an education abroad program on the intercultural learning and cross-cultural adaptability skills of university undergraduates. Issue 2 (2nd July 2020) - Fong, Jennifer
Abstract : Purpose: The purpose of this case study is to explore to what extent US university undergraduates participating in a research abroad program through US–Taiwan Partnerships for International Research and Education (PIRE) developed intercultural awareness and cross-cultural adaptability skills. It also suggests additional program design features to enhance students' international experiences. Design/methodology/approach: To better understand participants' experiences in the PIRE program, this study adopts a mixed-methods approach. Demographic questionnaires, pre- and postsurveys, observational field notes and individual interviews were conducted for data collection and analysis. Findings: Students perceived the experience abroad to improve their intercultural awareness and skills such as openness to cultural differences, coping with challenges abroad and effectively working in diverse teams. Specifically, quantitative findings reflected group gains in the areas of flexibility/openness and perceptual acuity, whereas qualitative findings indicated growth in students' emotional resilience and personal autonomy. Research limitations/implications: Additional data collection methods, such as pre-/postinstruments or a longitudinal study would provide a more comprehensive assessment of the impact of education abroad on students' intercultural learning. Social implications: Evaluation of programs and outcomes can help identify areas to maximize student learning and assess the value of education abroad. Originality/value: This is original research and makes a contribution to education abroad programs in postsecondary education.